Primeira República, poder local e a saga parlamentar para um novo código administrativo - Alves, Jorge Fernandes (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article analyzes the way of the parliamentary discussion about a new administrative code set to republican ideals. We conjure up the ideological heritage of the Republican movement at the time of advertising. We stress the decision to create a draft code. We indicate some of the vicissitudes of the discussion in parliament, the main topics of discussion and legislative outcomes. The administrative code of the First Republic proposed by the House of Representatives never approved in full at the Senate. It was issued an administrative law ((Administrative Law No. 88 of 07.08.1913), but it contains only some of the items provided in the project. So, the First Republic did not alter the previously established framework of centralist trend, and the promises of federation, decentralization and local autonomy were forgotten.